Bile Duct Injuries Following Laparoscopic Cholecystectomy - Khalil, Mohammad Ibrahim; Saha, Haridas; Chowdhury, Azmal Kader; Hossain, Imarat; Hossain, AZM Mostaque (Journal of Science Foundation, 2018)
Background: Laparoscopic cholecystectomy (LC) is the gold standard procedure for the gall stone diseases. Objective: This study aimed to assess the outcome of laparoscopic cholecystectomy (LC) by determining the frequency of complications especially of bile duct injuries. Methodology: This retrospective study was conducted in the Department of surgery at Dhaka Medical College and Hospital, Dhaka, Bangladesh. The case files of all patients undergoing laparoscopic cholecystectomy (LC) from the year of 2013 to 2015 were retrospectively analyzed. The data were collected according to outcome measures, such as bile duct injury, morbidity, mortality and numbers of patients whose resections had to be converted from laparoscopic to open surgery. Results: During the three years a total number of 336 patients were underwent LC for chronic cholecystitis (CC) of which 22(6.5%) developed complications. Among those who developed complications, two patients had major bile duct injuries (0.4%); other 43(12.8%) patients had planned laparoscopic operations converted to open cholecystectomy intra-operatively. None of the patients in this study died as a result of LC. Conclusion: The two patients who had severe common bile duct injury in this study had major anatomical anomalies that were only recognized during surgery. Journal of Science Foundation 2017;15(1):14-19